Morphometric Analysis of Camelid Remains from the Alero Deodoro Roca (ADR) Site (Córdoba, Argentina). An Attempt to Characterise Body-Size Variability in Sierras Pampeanas Australes Region - Silva Ferreira Da Costa, Thiago (2017)
This paper focuses in the morphometric analyses of Lama guanicoe remains recovered from the hunter–gatherer archaeological site Alero Deodoro Roca, located at Sierras Pampeanas Australes region (Córdoba Argentina), an area that has little information on the body-size variability of these artiodactyls. Because of the sparse osteometric data in the region, we focused on determining inter-intraspecific differentiation of wild camelids through corroborated osteometric techniques and multivariate statistical analyses of proximal phalanges. Our results showed a clear interspecific differentiation between modern vicuñas and archaeological specimens. We could also distinguish at least three guanaco size groups (small, medium and large) with the archaeological remains from the late Holocene (3000–3600 bp) of the site, presenting medium-size characteristics. Finally this paper aims at establishing a first approach in the characterisation of guanaco body size in the mountainous region of Córdoba.